Molecular residual disease detection in resected, muscle-invasive urothelial cancer with a tissue-based comprehensive genomic profiling–informed personalized monitoring assay - Powles, Thomas; Young, Amanda; Nimeiri, Halla; Madison, Russell W.; Fine, Alexander; Zollinger, Daniel R.; Huang, Yanmei; Xu, Chang; Gjoerup, Ole V.; Aushev, Vasily N.; Wu, Hsin-Ta; Aleshin, Alexey; et al. (Frontiers in Oncology, 2023)
Despite neoadjuvant therapy approaches and radical cystectomy, muscle-invasive bladder cancers frequently recur postoperatively. Recent data suggests that early detection of postsurgical molecular residual disease (MRD) using circulating tumor DNA (ctDNA) analysis may enable appropriate patient risk stratification and timely adjuvant treatment decision-making. Here, we tested a new tissue-informed personalized ctDNA monitoring assay, which does not require germline sequencing to filter nontumor variants. Retrospective analysis of patients from the IMvigor010 trial, a randomized adjuvant study comparing atezolizumab with observation in patients with bladder cancer after resection, showed that ctDNA positivity at the postsurgical time point was associated with recurrence and poor survival outcomes in the observation arm. Patients who were ctDNA-positive postoperatively and received adjuvant immunotherapy showed improved outcomes compared with those who were placed in observation. Our data supports the use of ctDNA analysis to detect MRD in patients with bladder cancer after surgery to guide adjuvant therapy.